General practitioners' and nurses' views on medication reviews and potentially inappropriate medicines in elderly patients - a qualitative study of reports by educating pharmacists - K. Schmidt-Mende; J. Hasselström; B. Wettermark; M. Andersen; P. Bastholm-Rahmner (Taylor & Francis Group, 2018)
Objective: The aim with this study was to understand more about how general practitioners (GPs) and nurses in primary care experience their work with medication reviews in elderly patients. Design: This qualitative study was nested within a cluster randomised trial and analysed narrative and unstructured diaries written by two pharmacists who performed academic detailing, i.e. educational outreach visits in primary care. The educational sessions dealt with potentially inappropriate medicines, and stimulated interprofessional dialogue in relation to medication reviews. The purpose of the diaries was to document and structure the pedagogical process of academic detailing and contained quotes from 194 GP and 113 nurse participants in the sessions, and the pharmacists' reflections. The data was explored using thematic analysis. Setting: Thirty-three primary care practices in Stockholm, Sweden. Subjects: GPs and nurses working in primary care. Main outcome measures: Thematic descriptions of academic detailing by pharmacists. Results: Five themes were identified: 1) Complexity in 3 'P': patients, pharmacotherapy, and primary care; 2) What, when, who? Clash between GPs' and nurses' experiences and guidelines; 3) Real-world problems and less-than-ideal solutions; 4) Eureka? Experiences with different steps during a medication review; and 5) Threats to GP autonomy. Conclusion: GPs and nurses should participate in the construction and release of guidelines in order to increase their usability in clinical practice. Future research should analyse if alternative strategies such as condensed medical reviews and feedback on prescribing are easier to implement in primary care.Key points Complex medication reviews have been introduced on a large scale in Swedish primary care, but knowledge on GPs' and nurses' views on such reviews is lacking. In the context of primary care alternative strategies such as condensed medication reviews and feedback on prescribing may be more applicable than medication reviews according to guidelines. GPs and nurses should make contributions to the development of guidelines on medication reviews in order to increase their usability in clinical practice.